Delegitimisation of Identity as a Political Strategy: The Moroccan Official Discourse about the Polisario Front - Barata, Maria João (2013)
This article focuses on the Moroccan government’s attempt to construct the Polisario Front as a potential terrorist group and considers this attempt as a strategy of delegitimisation of this nationalist movement. It analyses the way in which the issue of the Western Sahara is addressed in the Moroccan dominant discourse, and specifically with regard to the identity of Polisario. The aim is to grasp the repercussions of this strategy on the Moroccan interior politics as well as among the international actors and forums that can leverer the resolution of the issue over the sovereignty on the Western Sahara.